The Development of a Multilingual Tool for Facilitating the Primary-Specialty Care Interface in Low Resource Settings: the MSF Tele-Expertise System - Bonnardot, Laurent; Liu, Joanne; Wootton, Elizabeth; Amoros, Isabel; Olson, David; Wong, Sidney; Wootton, Richard (Frontiers in Public Health, 2014)
In 2009, Médecins Sans Frontières (MSF) started a pilot trial of store-and-forward telemedicine to support field workers. One network was operated in French and one in English; a third, Spanish network was brought into operation in 2012. The three telemedicine pilots were then combined to form a single multilingual tele-expertise system, tailored to support MSF field staff. We conducted a retrospective analysis of all telemedicine cases referred from April 2010 to March 2014. We also carried out a survey of all users in December 2013. A total of 1039 referrals were received from 41 countries, of which 89% were in English, 10% in French and 1% in Spanish. The cases covered a very wide range of medical and surgical specialties. The median delay in providing the first specialist response to the referrer was 5.3 hour (interquartile range 1.8, 16.4). The survey was sent to 294 referrers and 254 specialists. Of these, 224 were considered as active users (41%). Out of the 548 users, 163 (30%) answered the survey. The majority of referrers (79%) reported that the advice received via the system improved their management of the patient. The main concerns raised by referrers and specialists were the lack of support or promotion of system at headquarters' level and the lack of feedback about patient follow up. Because of the size of the MSF organisation it is clear that there is potential for further organisational adoption.